Peripheral nerve involvement in multiple sclerosis: Demonstration by magnetic resonance neurography - Jende, Johann; Pöhler, Gesa Helen; Diem, Ricarda; Weiler, Markus; Heiland, Sabine; Wildemann, Brigitte; Korporal-Kuhnke, Mirjam; Wick, Wolfgang; Pfaff, Johannes; Pham, Mirko; Bendszus, Martin; Hayes, Jennifer (Annals of neurology, 2017)
Objective To detect and quantify peripheral nerve lesions in multiple sclerosis (MS) by magnetic resonance neurography (MRN). Methods Thirty-six patients diagnosed with MS based on the 2010 McDonald criteria (34 with the relapsing-remitting form, 2 with clinically isolated syndrome) with and without disease-modifying treatment were compared to 35 healthy age-/sex-matched volunteers. All patients underwent detailed neurological and electrophysiological examinations. Three Tesla MRN with large anatomical coverage of both legs and the lumbosacral plexus was performed by using 2-dimensional (2D) fat-saturated, T2-weighted (T2w) and dual echo turbo spin echo sequences as well as a 3D T2-weighted, fat-saturated SPACE sequence. Besides qualitative visual nerve assessment, a T2w signal quantification was performed by calculation of proton spin density and T2 relaxation time. Nerve diameter was measured as a morphometric criterion. Results T2w hyperintense nerve lesions were detectable in all MS patients, with a mean lesion number at thigh level of 151.5 ± 5.7 versus 19.1 ± 2.4 in controls (p < 0.0001). Nerve proton spin density was higher in MS (tibial/peroneal: 371.8 ± 7.7/368.9 ± 8.2) versus controls (tibial/peroneal: 266.0 ± 11.0/276.8 ± 9.7, p < 0.0001). In contrast, T2 relaxation time was significantly higher in controls (tibial/peroneal: 82.0 ± 2.1/78.3 ± 1.7) versus MS (tibial/peroneal: 64.3 ± 1.0/61.2 ± 0.9, p < 0.0001). Proximal tibial and peroneal nerve caliber was higher in MS (tibial: 52.4 ± 2.1mm2, peroneal: 25.4 ± 1.3mm2) versus controls (tibial: 45.2 ± 1.4mm2, p < 0.0015; peroneal: 21.3 ± 0.7mm2, p = 0.0049). Interpretation Peripheral nerve lesions could be visualized and quantified in MS in vivo by high-resolution MRN. Lesions are defined by an increase of proton spin density and a decrease of T2 relaxation time, indicating changes in the microstructural organization of the extracellular matrix in peripheral nerve tissue in MS. By showing involvement of the peripheral nervous system in MS, this proof-of-concept study may offer new insights into the pathophysiology and treatment of MS. Ann Neurol 2017;82:676-685